2016
DOI: 10.5620/eht.e2016017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between residential district and health-related quality of life in Chungnam industrial complex area

Abstract: ObjectivesThis study aimed to evaluate the relationship between residential district of people, such as power plant, steel-mill and petrochemical industries, and health-related quality of life (HRQoL).MethodsUsing a cross-sectional study design, we randomly recruited participants for our study from industrial areas (thermoelectric power plant, steel-mill, petrochemical industry) and rural areas. Logistic regression analysis was used to identify the relationships between Euro quality of life-5 dimension (EQ-5D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…PA improves the HRQoL by improving physical function and lowering the risk of chronic diseases such as obesity and various diseases, thereby inducing fundamental health bene ts [24], as reported in earlier studies. An analysis of older adults 65 years and older in Korea showed that the physically active group had lower pain, pain interference, and fatigue than the inactive group [25].…”
Section: Discussionsupporting
confidence: 59%
“…PA improves the HRQoL by improving physical function and lowering the risk of chronic diseases such as obesity and various diseases, thereby inducing fundamental health bene ts [24], as reported in earlier studies. An analysis of older adults 65 years and older in Korea showed that the physically active group had lower pain, pain interference, and fatigue than the inactive group [25].…”
Section: Discussionsupporting
confidence: 59%
“…[12][13][14] Additionally, there was an imbalance in health status depending on the area of residence. [15][16][17] Medically underserved areas (MUAs) are "geographic locations, which has insufficient health resources to meet the medical needs of the resident population". 18 MUAs are defined using the time relevance Index (TRI), a proven index of accessibility, to identify places with low accessibility and poor quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the EQ-5D index was calculated using the Korean quality-weighting formula, and a value closer to 1 indicates a better HRQoL 30 . In this study, because there was no fixed cutoff point to define poor quality of life, a cutoff point from another study was used 31 : the lower 10% fractile was used to indicate poor HRQoL.…”
Section: Methodsmentioning
confidence: 99%